Responses Analysis of Tubular Joints in Offshore Substation Jacket due to Settlement During the Roll Up Process - Wildan Malika Candra Alfatih; Daniel Mohammad Rosyid; Rudi Walujo Prastianto (International Journal of Offshore and Coastal Engineering, 2026)
The Offshore Substation plays a crucial role in ensuring the success of Offshore Wind Farm systems in the clean energy transition. During the fabrication stage, the jacket structure used as the Offshore Substation undergoes a fabrication process known as roll-up. During this roll-up process, ground settlement at the fabrication yard may occur, causing the jacket structure to tilt and increasing the risk of structural failure, which can reduce the effectiveness of the jacket structure’s integrity. In this study, a roll-up analysis of the jacket structure was conducted using SACS software with variations in roll-up angles of 0°, 30°, 45°, 60°, 75°, and 96.4°. The analysis results indicate that during the roll up process under settlement conditions, several critical areas were identified, particularly at the K-joint and X-joint, with maximum unity check (UC) values of 0.994 and 0.982, respectively. Further investigation was carried out through a local analysis using finite element software. The local stresses obtained were 264.6 MPa at the X-joint and 323.9 MPa at the K-joint. Since the stress at the K-joint exceeded the allowable stress, a thickness increase of 10 mm was applied to the brace experiencing the maximum stress. As a result, the stress was reduced by 172.29 MPa and was brought below the allowable stress limit.